ANALYSIS OF ACTINOMYCETES ABUNDANCE IN THE RHIZOSPHERE OF MANGROVE ECOSYSTEMS IN SEKOTONG AS A POTENTIAL SOURCE OF BENEFICIAL MICROBES - Sakaroni, Rubiyatna; Baiq Isti Hijriani; Wirdullutfi (Jurnal Biogenerasi, 2025)
The rhizosphere of mangroves is a microhabitat rich in root exudates and organic matter, making it an ideal environment for the growth of Actinomycetes. This study aims to analyze the abundance of Actinomycetes in the mangrove rhizosphere at three different locations in Sekotong District, West Lombok: Bagek Kembar, Tanjung Batu, and Buwun Mas. Sampling was conducted using purposive sampling in the dominant root zone at a depth of ±20 cm. Actinomycetes isolation was performed using the surface plate method on SCA medium supplemented with nystatin as an antifungal agent. The results showed that the highest abundance was found in the rhizosphere of Rhizophora mucronata at Bagek Kembar with 4.6 × 10⁵ CFU/g, while the lowest was in Avicennia marina at Tanjung Batu with 1 × 10⁵ CFU/g. In general, Rhizophora mucronata showed higher abundance than Avicennia marina in all locations. This difference was influenced by root exudate characteristics, root system structure, and soil physicochemical conditions such as aeration and organic matter content. This study concludes that the rhizosphere of Rhizophora mucronata in Bagek Kembar is a more supportive habitat for the growth of Actinomycetes. This finding serves as an important basis for further exploration of Actinomycetes isolates from mangroves as potential sources of biocontrol agents and antimicrobial compound producers.